Implementasi Metode Bercerita Dalam Meningkatkan Perkembangan Bahasa Anak Usia Dini Di TK Swasta Al-Ihsan - Febe Wahyuni Br. Sihoming; Dina Amanda; Nida Afifah; Nabila Dhara; Anggia Puteri (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Early childhood language development is one of the abilities that children must have as a means of communicating and interacting with their environment. The aim of this research is to describe storytelling methods to improve language development skills in early childhood. The subjects of this research involved 8 students from Al-Ihsan Private Kindergarten, of whom two children had speech delays. The research methods used were observations and interviews with teachers as well as observations at the Al-Ihsan private kindergarten. The results of this research show that the storytelling method can improve the language development of young children aged 4-6 years through children's stories, which can develop creative imagination and can also help children communicate